2001
DOI: 10.1126/science.1058424
|View full text |Cite
|
Sign up to set email alerts
|

Massive Expansion of Marine Archaea During a Mid-Cretaceous Oceanic Anoxic Event

Abstract: Biogeochemical and stable carbon isotopic analysis of black-shale sequences deposited during an Albian oceanic anoxic event (approximately 112 million years ago) indicate that up to 80 weight percent of sedimentary organic carbon is derived from marine, nonthermophilic archaea. The carbon-13 content of archaeal molecular fossils indicates that these archaea were living chemoautotrophically. Their massive expansion may have been a response to the strong stratification of the ocean during this anoxic event. Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
136
2
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 243 publications
(157 citation statements)
references
References 20 publications
10
136
2
9
Order By: Relevance
“…Gene copies at 450 m were comparable to those in the upper portion of the water column, and reached 10 4 copies per milliliter in the Carmen Basin. Relatively high archaeal amoA abundances under suboxic conditions are in line with a number of previous studies: expansions of marine archaea may occur during oceanic anoxic events (Kuypers et al, 2001), archaeal amoA genes have been recovered from the OMZ of the ETNP and from the suboxic zone of the Black Sea (Francis et al, 2005), and archaeal amoA copy numbers were maximal in the suboxic zone of the Black Sea (Coolen et al, 2007;Lam et al, 2007). In an interesting parallel, the distribution of marine Crenarchaeota based on their membrane lipid, crenarchaeol, showed consistently high abundances at 450 m in the OMZ of the Arabian Sea (Sinninghe Damste et al, 2002).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Gene copies at 450 m were comparable to those in the upper portion of the water column, and reached 10 4 copies per milliliter in the Carmen Basin. Relatively high archaeal amoA abundances under suboxic conditions are in line with a number of previous studies: expansions of marine archaea may occur during oceanic anoxic events (Kuypers et al, 2001), archaeal amoA genes have been recovered from the OMZ of the ETNP and from the suboxic zone of the Black Sea (Francis et al, 2005), and archaeal amoA copy numbers were maximal in the suboxic zone of the Black Sea (Coolen et al, 2007;Lam et al, 2007). In an interesting parallel, the distribution of marine Crenarchaeota based on their membrane lipid, crenarchaeol, showed consistently high abundances at 450 m in the OMZ of the Arabian Sea (Sinninghe Damste et al, 2002).…”
Section: Resultssupporting
confidence: 91%
“…In particular, although marine Crenarchaeota have been shown to numerically dominate microbial communities throughout the water column (DeLong et al, 1994;Karner et al, 2001), there has been limited insight into the biogeochemical and ecological roles of these organisms following their initial identification in the ocean (DeLong, 1992;Fuhrman et al, 1992;Francis et al, 2007). Consistent with a role in nitrification-the stepwise oxidation of ammonia (NH 3 ) to nitrite (NO 2 À ) to nitrate (NO 3 À )-several studies have indicated that a large proportion of the Crenarchaeota are autotrophic (Kuypers et al, 2001;Pearson et al, 2001;Wuchter et al, 2003;Ingalls et al, 2006;Kirchman et al, 2007). Most convincingly, cultivation of the autotrophic ammonia-oxidizing archaeon (AOA) Nitrosopumilus maritimus confirmed that at least some mesophilic Crenarchaeota are capable of ammonia oxidation (Kö nneke et al, 2005), and archaeal amoA genes appear to be widespread in water columns and sediments where nitrification is expected to be important (Francis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…GDGTs are preserved well in the sedimentary record and can thus be used as biomarkers for this group of Archaea (e.g. Kuypers et al, 2001;Pancost et al, 2001;Ingalls et al, 2006;Coolen et al, 2007). Schouten et al (2002) found a correlation between sea surface temperature (SST) and the distribution of four specific GDGTs present in sediment core tops (GDGT-1, -2, -3 and -4 0 , Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Upon cell death, most of these intact polar lipids (IPLs) are transformed into core lipids (CLs) via hydrolysis of the polar head groups (White et al, 1979). This supposedly rapid loss of functional groups resulted in their use as suitable markers for living cells, in contrast to the core lipids, which can be preserved over geological timescales of millions of years (e.g., Kuypers et al, 2001;Jenkyns et al, 2012). Considerable amounts of IPL GDGTs (10 -10 000 ng g -1 sediment) were found in shallow to deeply buried marine sediments [0.7 to 121 m below sea floor (mbsf)], which suggests the presence of a large number of living archaeal cells (Biddle et al, 2006;Lipp et al, 2008;Lipp and Hinrichs, 2009).…”
Section: Introductionmentioning
confidence: 99%